Using Quizizz Application for Learning and Evaluating Grammar Material - Dian Fadhilawati (Universitas Islam Balitar, 2021)
This research aims to enhance the students’ grammar achievement in learning relative pronouns by applying quizizz application The Subjects of the research are 24 students of Second semester who take Intermediate English Grammar Course in Balitar Islamic University. The design of the research is classroom action reseach which covers 4 main steps: Planning, Acting, Observing, and Evaluating.The researcher uses test and Questionnaire for gaining the data of the research. The research findings shows that the students’ achievement in learning relative pronouns increase after they learned the materials and evaluated by applying quizizz Application. Moreover, they’ also present positive views to the use of Quizizz for Learning and evaluating Relative Pronouns.